Artificial intelligence in retinal screening using OCT images: A review of the last decade (2013-2023) - Akpinar, Muhammed Halil; Sengur, Abdulkadir; Faust, Oliver; Tong, Louis; Molinari, Filippo; Acharya, U. Rajendra (Elsevier Ireland Ltd, 2024)
Background and objectives: Optical coherence tomography (OCT) has ushered in a transformative era in the domain of ophthalmology, offering non-invasive imaging with high resolution for ocular disease detection. OCT, which is frequently used in diagnosing fundamental ocular pathologies, such as glaucoma and age -related macular degeneration (AMD), plays an important role in the widespread adoption of this technology. Apart from glaucoma and AMD, we will also investigate pertinent pathologies, such as epiretinal membrane (ERM), macular hole (MH), macular dystrophy (MD), vitreomacular traction (VMT), diabetic maculopathy (DMP), cystoid macular edema (CME), central serous chorioretinopathy (CSC), diabetic macular edema (DME), diabetic retinopathy (DR), drusen, glaucomatous optic neuropathy (GON), neovascular AMD (nAMD), myopia macular degeneration (MMD) and choroidal neovascularization (CNV) diseases. This comprehensive review examines the role that OCT-derived images play in detecting, characterizing, and monitoring eye diseases. Method: The 2020 PRISMA guideline was used to structure a systematic review of research on various eye conditions using machine learning (ML) or deep learning (DL) techniques. A thorough search across IEEE, PubMed, Web of Science, and Scopus databases yielded 1787 publications, of which 1136 remained after removing duplicates. Subsequent exclusion of conference papers, review papers, and non -open -access articles reduced the selection to 511 articles. Further scrutiny led to the exclusion of 435 more articles due to lowerquality indexing or irrelevance, resulting in 76 journal articles for the review. Results: During our investigation, we found that a major challenge for ML -based decision support is the abundance of features and the determination of their significance. In contrast, DL -based decision support is characterized by a plug -and -play nature rather than relying on a trial -and -error approach. Furthermore, we observed that pre -trained networks are practical and especially useful when working on complex images such as OCT. Consequently, pre -trained deep networks were frequently utilized for classification tasks. Currently, medical decision support aims to reduce the workload of ophthalmologists and retina specialists during routine tasks. In the future, it might be possible to create continuous learning systems that can predict ocular pathologies by identifying subtle changes in OCT images.
Keywords: Optical coherence tomography; Eye disease diagnosis; Machine learning; Deep learning